2007
DOI: 10.1007/s00572-007-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differential in vitro responses to Ni in Cenococcum geophilum isolates from serpentine soils in Portugal

Abstract: Amplified fragment length polymorphism (AFLP) analysis was used to investigate the genetic diversity in isolates of the ectomycorrhizal fungus Cenococcum geophilum from serpentine and non-serpentine soils in Portugal. A high degree of genetic diversity was found among C. geophilum isolates; AFLP fingerprints showed that all the isolates were genetically distinct. We also assessed the in vitro Ni sensitivity in three serpentine isolates and one non-serpentine isolate. Only the nonserpentine isolate was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…As a result of competition, Ni at high concentrations may inhibit the absorption of these metals, decreasing their concentration and even leading to their deficiency in plants (Ahmad et al 2007;Van Assche and Glijsters 1990;Rubio et al 1994). Subsequently, this may affect important physiological processes, and ultimately result in toxic effects (Gajewska et al 2006;Gon_alves 2007). For example, Ni can decrease Mg (or Fe) uptake and its supply to aerial parts via competition, and then induce deficiencies of these elements in plants.…”
Section: Interference With Other Essential Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of competition, Ni at high concentrations may inhibit the absorption of these metals, decreasing their concentration and even leading to their deficiency in plants (Ahmad et al 2007;Van Assche and Glijsters 1990;Rubio et al 1994). Subsequently, this may affect important physiological processes, and ultimately result in toxic effects (Gajewska et al 2006;Gon_alves 2007). For example, Ni can decrease Mg (or Fe) uptake and its supply to aerial parts via competition, and then induce deficiencies of these elements in plants.…”
Section: Interference With Other Essential Metal Ionsmentioning
confidence: 99%
“…This can result in the retardation of germination, growth suppression, and reductions in yields (Madhava Rao and Sresty 2000;Seregin and Kozhevnikova 2006a, b). These inhibitory effects of Ni on the growth of plants can be reduced by supplying additional Mg (or Fe) ions (Genrich et al 1998;Gon_alves 2007;Ouzounidou et al 2006). Therefore, Ni toxicity in plants is partly due to interference with other essential metal ions.…”
Section: Interference With Other Essential Metal Ionsmentioning
confidence: 99%
“…Although multilocus genotype assessments suggest the occurrence of recombination and a possible cryptic sexual cycle (Taylor et al 1999, Lobuglio and Taylor 2002, Douhan et al 2007), a sexual stage has so far been assumed to be absent in C. geophilum (although see Fernandez-Toiran andAgueda 2007, andSpatafora et al 2012). While this absence would imply clonal reproduction and a relatively low genetic diversity, various studies have demonstrated an unexpectedly high level of genetic diversity within and between C. geophilum populations (e.g., Panaccione et al 2001;Wu et al 2005;Douhan et al 2007;Gonçalves et al 2007).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…geophilum has been shown to be locally adapted to serpentine soil conditions (Gonçalves et al 2007(Gonçalves et al , 2009. Serpentine soils are widespread soils formed by the weathering of ultramafic rocks and typically have a low calcium-to-magnesium ratio, with calcium levels significantly lower compared to surrounding non-serpentine soils.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In one study all isolates of Paxillus involutus were less tolerant to Zn, than any of those of Amanita muscaria (Brown and Wilkins 1985) and also, it was demonstrated that while radial growth of a Suillus bovinus isolate was inhibited by 91% when exposed to 0.5 ppm cadmium, while Paxillus involutus and Rhizopogon subcaerulescens were only inhibited by approximately 26 and 28%, respectively (Kim et al 2004). Also, four isolates of C. geophilum demonstrated a range of sensitivities to nickel (Goncalves et al 2007). A similar response was observed for Cu: Paxillus involutus and Laccaria laccata grew at 2.5 ppm Cu, whereas the concentration had to be decreased 10-fold before any growth of Scleroderma citrinum…”
Section: Discussionmentioning
confidence: 98%